Quality of life of the mechanically ventilated patients with community-acquired pneumonia - Zornić, Nenad; Milovanović, Dragan; Stojadinović, Miroslav; Radovanović, Dragče; Davidović, Goran; Simović, Stefan; Bukumirić, Zoran; Janjić, Vladimir; Marić, Nebojša; Jevdjić, Jasna; Rosić, Vesna; Nešić, Jelena (Vojnosanitetski pregled, 2020)
Background/Aim. Patients with pneumonia who require mechanical ventilation (MV) are associated with several poor outcomes such as prolonged hospitalization, higher rate of mortality and increased spread of antibiotics-resistant pathogens. MV in patients with community-acquired pneumonia (CAP) could cause development of psychological symptoms, often neglected in the Intensive Care Units (ICU) as well as decreased quality of life after the withdrawal of the MV. The aim of the study was to evaluate the quality of life in patients with CAPs treated with MV in ICU. Methods. The study was designed as a cohort study of hospital-treated patients with CAP with prospective data collection. The quality of life was defined as the primary outcome, while the use of MV was assumed as the primary prognostic factor that adversely affected the outcome. The patients were recruited from the population of patients with CAPs who were hospitalized at the ICU, Clinical Center Kragujevac, Serbia, from January 2013 to January 2014. The experimental group consisted of patients who were on MV while the control group included patients who were treated for CPAs in the ICU, but were not subjected to MV. The quality of life was assessed by using patient-rated Euro Quality of Life (EuroQoL) Group-EQ-5D index. The calculation of the total EQ-5D-5L score values was performed by using the predefined, validated mapping key according to response combinations. Statistical analysis was performed by using χ2 test, Student's t-test, univariate and multivariate logistic regression analyses. Results. The patients with MV had worse EQ5D-5L values in comparison to the control group for all 5 domains. Mobility, self-care and usual activities were negatively affected during the whole follow-up period. Pain or discomfort and anxiety or depression differed significantly between the study group and the control group at days 7 and 30. Conclusion. Patients with MV tend to have poorer quality of life, especially in 3 domains. The main reasons are the presence of chronic comorbidities in the population that require MV.
Keywords: respiration, artificial; pneumonia; critical care; quality of life; prognosis.